Multicountry review: developmental surveillance, assessment and care by outpatient paediatricians. Issue 3 (28th June 2022) - Coscini, Nadia; Heyes, Priya; Bedford, Helen; Cohen, Eyal; D'Aprano, Anita; Goldfeld, Sharon; Hargreaves, Dougal; Loveday, Sarah; Nejat, Sahar; Roberts, Gehan; Sarkadi, Anna; Saunders, Natasha Ruth; et al.
Abstract : Background: Care of young children with neurodevelopmental disorders (NDD) is a major component of paediatric outpatient practice. However, cross-country practice reviews to date have been limited, and available data demonstrate missed opportunities for early identification, particularly in vulnerable population subgroups. Methods: Multicountry review of national paediatric body guidance related to developmental surveillance, early identification and early childhood intervention together with review of outpatient paediatrician practices for developmental assessment of children aged 0–5 years with/at risk of NDDs. Review included five countries with comparable nationalised universal child healthcare systems (ie, Australia, Canada, New Zealand, Sweden and the UK). Data were collected using a combination of published and grey literature review, supplemented by additional local sources with descriptive review of relevant data points. Results: Countries had broadly similar systems for early identification of young children with NDDs alongside universal child health surveillance. However, variation existed in national paediatric guidance, paediatric developmental training and practice, including variable roles of paediatricians in developmental surveillance at primary care level. Data on coverage of developmental surveillance, content and quality of paediatric development assessment practices were notably lacking. Conclusion: Paediatricians play an important role in ensuring equitable access to early identification and intervention for young children with/at risk of NDDs. However, strengthening paediatric outpatient care of children with NDD requires clearer guidance across contexts; training that is responsive to shifting roles within interdisciplinary models of developmental assessment and improved data to enhance equity and quality of developmental assessment for children with/at risk of NDDs.